TYPES OF SA’J ART AND ITS APPLICATION IN UZBEK LITERATURE - Djumayeva Baxtiniso To‘raqulovna (Web of Journals Publishing, 2024)
This article provides information about the types of sa’j, the characteristics considered when categorizing these types, and its application in Uzbek literature.
Keywords: parallel sa’j, rhymed sa’j, balanced sa’j, complete sa’j, rhyme, rawi, rhythm.